2022
DOI: 10.3390/digital2020008
|View full text |Cite
|
Sign up to set email alerts
|

Design of Open Code Software to Downs and Steiner Lateral Cephalometric Analysis with Tracing Landmarks

Abstract: Cephalometric analysis is an excellent instrument in clinical diagnosis, treatment, and recovery from surgery. Nowadays, efforts to develop computerized dental X-ray image Cephalometric analysis systems for clinical and education usages. Much commercial software is created, but its high cost is unaffordable for some undergraduate students or low-income medical institutions; sure, the best option is the use of open source software alternatives. The study aimed to design free software Cephalopoint that applies v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As for the authors, only O’Toole ( 22, 23 ) matches 2 (5.1%) articles as first author. The years of publication of the articles ranged from 2015 to 2023, with 2022 predominating ( 17, 18, 21, 24, 25, 26, 27, 28, 29, 30 ) with 10 (25.6%) reports.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As for the authors, only O’Toole ( 22, 23 ) matches 2 (5.1%) articles as first author. The years of publication of the articles ranged from 2015 to 2023, with 2022 predominating ( 17, 18, 21, 24, 25, 26, 27, 28, 29, 30 ) with 10 (25.6%) reports.…”
Section: Resultsmentioning
confidence: 99%
“…As for the authors, only O'Toole (22,23) matches 2 (5.1%) articles as first author. The years of publication of the articles ranged from 2015 to 2023, with 2022 predominating (17,18,21,24,25,26,27,28,29,30) with 10 (25.6%) reports. Table 3 shows the relationship of computer tools described by the articles with the country where they were developed, year of creation, programming language, platforms on which they can be used, the specialty with which they are related, whether they were validated, are open source, are free and the payment model to which they are subject.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of n = 20 studies were identified fulfilling the inclusion and exclusion criteria within the timeframe of 2013 to 2023 [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The year-wise distribution of these studies is depicted in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%